Australian Mining Transformation and Future Prospects in Response to the 4th Industrial Revolution - Jang, Hyong Doo (The Korean Society of Mineral and Energy Resources Engineers, 2019)
Demands for minerals have been significantly increased through industrial developments and mineable resources near the surface have been nearly depleted. Meanwhile, the mining industry is facing new challenges including, low-grade ore, orebodies in deep depth, and rigorous environmental constraints. In addition, the accountabilities of significant social challenges and sustainable development in the mining sector increased economic burdens to mining companies. These challenges can be surmounted with technical improvements and optimization of the whole mining value chain utilizing advanced ICTs and automation technologies. The aims of the study are to stimulate the mining industry in South Korea and present future prospects of the mining industry through reviewing the sustainable development in mining, the global trend of mining innovations and major mining companies, and some of new ICTs and data-based mining technologies in Australia.